2021
DOI: 10.3389/fcell.2021.716208
|View full text |Cite
|
Sign up to set email alerts
|

ORF3a-Mediated Incomplete Autophagy Facilitates Severe Acute Respiratory Syndrome Coronavirus-2 Replication

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the causative agent for the coronavirus disease 2019 (COVID-19) pandemic and there is an urgent need to understand the cellular response to SARS-CoV-2 infection. Beclin 1 is an essential scaffold autophagy protein that forms two distinct subcomplexes with modulators Atg14 and UVRAG, responsible for autophagosome formation and maturation, respectively. In the present study, we found that SARS-CoV-2 infection triggers an incomplete autophagy respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 49 publications
8
104
1
Order By: Relevance
“…The results of this multi-omics study are in agreement with our findings, showing that SARS-CoV-2 regulates mTOR activity and autophagy at different levels. Nonetheless, another study showed that SQSTM1/p62 levels did not change during SARS-CoV-2 infection [21]. We demonstrated that the ratio of the autophagosome markers LC3-II to LC3-I and the content of p62/SQSTM1 increase in infected cells (Figure 1A), which is associate with the accumulation of autophagosomes by blockage of the autophagy flux [22].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The results of this multi-omics study are in agreement with our findings, showing that SARS-CoV-2 regulates mTOR activity and autophagy at different levels. Nonetheless, another study showed that SQSTM1/p62 levels did not change during SARS-CoV-2 infection [21]. We demonstrated that the ratio of the autophagosome markers LC3-II to LC3-I and the content of p62/SQSTM1 increase in infected cells (Figure 1A), which is associate with the accumulation of autophagosomes by blockage of the autophagy flux [22].…”
Section: Discussionmentioning
confidence: 63%
“…The cell-to-cell transfer of viral components demonstrated here might represent an additional mechanism that SARS-CoV-2 uses to infect new cells while escaping the immune system and shed light on the virulence mechanisms and transmissibility SARS-CoV-2. For example, viral particle accumulation inside cells could explain cases of persistent systemic infection by SARS-CoV-2, the late onset of the symptoms, and the fact that many asymptomatic individuals are still able to produce infectious viral particles [21,85,86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation raises the question of using this membrane reservoir for viral replication and as a way to hide from the immune system. This might be a partial answer in determining DMV origins in the case of SARS-CoV-2 ( 9 ). For SARS-CoV-2, the DMVs were very well characterized thanks to recent high-resolution microscopy techniques: DVMs are composed of two membranes separated by 18-nm luminal spacing, with an average diameter of 340 nm for the inner membrane, similar to SARS-CoV-1 DMVs ( 7 ).…”
Section: Viral Rna Replication Occurs In Double-membrane Vesiclesmentioning
confidence: 99%
“…Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), an enveloped, single-stranded and positive-sense RNA β-coronavirus, is the cause of the COVID-19 pandemic (Wang et al, 2020;Wu et al, 2020;Zhou et al, 2020). ORF3a, an accessory protein of SARS-CoV-2, could strongly inhibit autophagy activity by blocking the fusion of autophagosomes with lysosomes (Hayn et al, 2021;Miao et al, 2021;Qu et al, 2021;Zhang et al, 2021). Specifically, ORF3a is localized in the late endosome and directly interacts with and sequestrates VPS39, an essential component of the homotypic fusion and protein sorting (HOPS) complex, thereby preventing the FIGURE 4 | Viruses hijack and subvert host autophagy to aid their own infections and pathogenesis.…”
Section: Viruses Counter Host Autophagy By Inhibiting the Autophagy Downstream Degradation Pathwaymentioning
confidence: 99%